Review of the History of Materials Used With Experience with Bone Cement Cranioplasty - Roka, Yam Bahadur (Nepal Journal of Neuroscience, 2017)
Cranioplasty is the surgical repair of cranial defect or deficiency of the skull with a aim for functional and cosmetic improvement. Inorganic and organic materials have both been used for cranioplasty with the ideal cranioplasty material is yet to be made or discovered with present focus of research on molecular biology. This article does a brief review of the history of materials used and discusses the results of the use of bone cement cranioplasty (BCC) in this centre. A total of 61 cases were included in the study with the majority being males (44 cases). Road traffic accident was the most common initial cause of injury (45 cases), followed by fall (10 cases) and physical assault in the rest. On admission and based on the GCS based head injury classification the majority were in the severe head injury type (GCS<8) in 44 cases followed by moderate head injury in the rest. The majority of the decompressive craniectomy was done on the left side (32 cases) followed by right (22 cases) and bilateral in 7 cases (including single fl apbifrontal in 5 cases). In our centre as for other centres in Nepal and developing countries, bone cement remains the best, safest, cheapest choice along with autologous graft for cranioplasty. Nepal Journal of Neuroscience, Volume 14, Number 1, 2017, Page: 7-13